Locus de controle e a efetividade empresarial em microempresários do estado do Rio Grande do Norte - Oliveira, João Maria de (2010)
Entrepreneurs are individuals who can transform economic and social realities by promoting development, so it became important tools in generating externalities in regions where they operate. In Brazil, 59.9% of new ventures do not reach the fourth year of life, the mortality rate of new ventures is high. The causes of mortality are numerous, and within the behavioral aspects, one is the locus of control. This study determines the degree of association between internal locus of control and achieving business success of entrepreneurs in Rio Grande do Norte who participated in the workshop EMPRETEC. The approach that studies the behavior entrepreneurs agreed that there are psychological characteristics associated with a set of values, attitudes and needs that determine the behavior and induce the entrepreneur to achieve success. Among these features is the locus of control, a skill that individuals must identify in their actions, or lack of them, the causes of their successes and failures. The locus is external when the individual attributes to factors outside themselves as causes of their results, and is built in when you can identify the actions that led to success. We surveyed 223 entrepreneurs statewide who answered the questionnaire for assessing the scale of locus of control, selfassessment questionnaire of entrepreneurial characteristics of EMPRETEC and a questionnaire assessing the business success. 71.9% were identified as having success. Among the behavioral characteristics strongest in the group of entrepreneurs are setting goals and commitment. Was found for locus of control mean value of 7.35, confidence interval between 7.05 and 7.66. Showing that the locus of control group is predominantly internal. We also found a correlation between the locus and commitment, between setting goals and commitment; calculated risks and information search; search of information and commitment, and between commitment and independence and self confidence. Dependence was not identified among the set of features and business success, determining the absence of an ideal profile. However, logistic regression significant association was found indicating that the smaller the individual's locus of control increased the likelihood of it achieving business success